Resistance training during pre- and early puberty: efficacy, trainability, mechanisms, and persistence - Blimkie, C. R. (Canadian Journal of Applied Sport Sciences, 1992)
Resistance training, under conditions of high intensity and volume loading, is effective in increasing strength in pre- and early pubertal children. The mechanisms underlying strength gain with resistance training in this population have not been established unequivocally. However, resistancce training appears to have little if any effect on muscle size (hypertrophy), but it has resulted in neurological (percent motor unit activation and increased integrated EMG activity) changes and changes in intrinsic muscle function (twitch torque), which could account for part of the training-induced increases in voluntary strength. Changes in motor skill coordination (synchronisation of muscle action) probably also contribute substantially to resistance-training-induced strength increases in children, particularly for multi-joint, complex strength manoeuvres. Most, but not all, studies indicate that pre- and early pubertal children make similar relative strength gains compared to adolescents and adults, but usually demonstrate smaller absolute strength gains following training. Training-induced strength gains appear to decay during detraining, and maintenance training consisting of only one training session per week appears to be ineffective in preserving prior strength gains.